2016
DOI: 10.1038/nmat4568
|View full text |Cite
|
Sign up to set email alerts
|

Orbital symmetry of charge-density-wave order in La1.875Ba0.125CuO4 and YBa2Cu3O6.67

Abstract: Recent theories of charge-density-wave (CDW) order in high-temperature superconductors have predicted a primarily d CDW orbital symmetry. Here, we report on the orbital symmetry of CDW order in the canonical cuprate superconductors La1.875Ba0.125CuO4 (LBCO) and YBa2Cu3O6.67 (YBCO), using resonant soft X-ray scattering and a model mapped to the CDW orbital symmetry. From measurements sensitive to the O sublattice, we conclude that LBCO has predominantly s' CDW orbital symmetry, in contrast to the d orbital symm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 47 publications
9
81
1
1
Order By: Relevance
“…With different experimental techniques (resonant X-ray scattering, hard X-ray diffraction, scanning tunneling microscopy(STM)) CDWs have been directly detected in underdoped samples of YBCO [1][2][3][4][5][6][7][8][9][10][11] , Bi-2201 12,13 , Bi-2212 [14][15][16][17][18][19] and, recently, Hg-1201 20,21 compounds. Additional input comes from indirect probes, such as transport measurements 22,23 and quantum resistance oscillations [24][25][26] consistent with a CDW-like reconstruction [27][28][29] of the Fermi surface (FS), nuclear magnetic resonance 30,31 , ultrasound propagation 32 and reflectivity oscillations in pump-probe experiments due to a collective CDW mode 33 .…”
Section: Introductionmentioning
confidence: 99%
“…With different experimental techniques (resonant X-ray scattering, hard X-ray diffraction, scanning tunneling microscopy(STM)) CDWs have been directly detected in underdoped samples of YBCO [1][2][3][4][5][6][7][8][9][10][11] , Bi-2201 12,13 , Bi-2212 [14][15][16][17][18][19] and, recently, Hg-1201 20,21 compounds. Additional input comes from indirect probes, such as transport measurements 22,23 and quantum resistance oscillations [24][25][26] consistent with a CDW-like reconstruction [27][28][29] of the Fermi surface (FS), nuclear magnetic resonance 30,31 , ultrasound propagation 32 and reflectivity oscillations in pump-probe experiments due to a collective CDW mode 33 .…”
Section: Introductionmentioning
confidence: 99%
“…This pair-density-wave phase is believed to have a d-wave pair-field which is large in the regions with excess holes and oscillates in sign between these charged regions 12,13 . Achkar et al 14 have reported resonant soft x-ray scattering measurements which show that the charge distribution on the oxygens of LBCO have an s -CDW orbital structure in which the charge modulations on the O px and O py sites in a unit cell are in phase. STM Studies of BSCCO (p ∼ 8%) and NaCCOC (p ∼ 12%) find that these materials have a predominantly d-CDW orbital form factor in which these O px and O py charge modulations are out of phase 15 .…”
mentioning
confidence: 99%
“…When additional holes are added they go ∼ 75% onto the O sites and charge stripes separated by π-phase shifted antiferromagnetic regions appear. The O hole occupation and the Cu spin structure has an s -CDW-SDW like structure 14 . When additional electrons are added, they go approximately 90% onto the Cu d x 2 −y 2 orbitals.…”
mentioning
confidence: 99%
“…The close connection between axial charge order with a d-wave form factor 31 and oxygen orbitals makes the three-band model a necessary starting point for the microscopic theory. In this context, the focus has so far been on spin fluctuations, and hence on the local Coulomb interactions U d and U p .…”
Section: Discussionmentioning
confidence: 99%
“…The ICO phase involves predominantly a charge transfer between oxygen orbitals in the CuO 2 planes [20][21][22]31,32 . This challenges notions of immutable CuO 2 bands, and points to the necessity to employ multiorbital models for the ICO phase [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%